Currency devaluation-induced inflation, university academic staff research output and coping strategies - Adeyanju, Joseph; Nwaodike, Chibuzor Ayodele; Aina, Ayandiji Daniel (African Journal of Stability and Development (AJSD), 2025)
Nigerian university academic staff are exposed to hostile economic environment of currency devaluation-induced inflation, which poses as a challenge to their ability to contribute to research and development. This study seeks to investigate how currency devaluation-induced inflation influences research output of Nigerian university academic staff and the coping strategies often employed by them. Through the use of sequential explanatory mixed method research design, with quantitative data obtained from 413 academic staff in 6 Nigerian universities; and qualitative data from documents and interviewee, the study found that as Naira value declines, academic research output declines in resonance. The study also found that academic staff employ diverse economic coping strategies for personal and research output mitigation. The study concludes that currency devaluation-induced inflation inimically affects academic staff research output, and despite adopted coping mechanism, none is significantly effective. The study recommends autochthonous corrective and mitigating pathways.